The Analysis of the Beauty Concept with Employing the Semantic Network - Sayyedeh Elham Aghaii Abrandabadi; Jamileh Alam al_Hoda (آموزه‌های قرآنی)
The present research with aim to analyze the concept of beauty in the holy Quran with applying the semantic network has been scheduled that is from perceiving the meaning of a concept through studying the related concepts as the important and specific aspects of that concept and their relations become visible. For achieving this general mentioned goal, the stages of the conceptology of the beauty lexicon and beautifying (being adorned), the recognition of the lexicon position, the recognition of the conceptual relation between lexicons, inferring the key concepts proportion to beauties and beautifying and at the end, the analysis of the concept of real beauty which is leaded to good and the real beauty which is leaded to evil and adornment has been formed. The method of research is the analysis based on the semantic network and for this aim, the verses of the holy Quran, the Quran exegeses and the authentic lexical books have been used. The results of this research are: it should be differentiated between the concepts of beauty which results good and the concepts of real beauty and adornment which results evil. The concept of beauty and adornment (beautifying) intensively are intertwined. In reality, the instance of beauty and adornment (being adorned) can be itself cause, effect or concurrent with the other beauties (and adornment). In other word, the beauty and adornment constantly develops and grows in the successive rings. These productive concepts (beauty or adornment) have been selected as the key concepts. In the analysis of the concept of the real beauty leading to good and the real beauty leading to evil with studying the common concepts of the ijabi (affirmative or positive) and salbi (privative or negative) relation and the illuminative relationship which are among these concepts, it should be mentioned that the concept of faith (iman) in God has a main position in the beauty leading to good. In the real beauty leading to evil and adornment although at the beginning they are completely different but at the end of the path they leaded to one point. in both, kufr (unbelief) has a crucial role.